Влияние сезонных и широтных изменений солнечного излучения на синтез пластидных пигментов - Коломиец, Ирина (CEP USM, 2024)
În lucrarea prezentată, folosind exemplul carotenoidelor și tetrapirolilor, este fundamentată condiționalitatea de mediu a sintezei pigmenților plastidieni. In seria omologică genului Viola, se arată că sinteza determinată genetic de carotenoide și tetrapiroli este o adaptare la ritmurile circadiene ale radiației solare și la variațiile caracteristicilor sale cantitative și calitative. Se încearcă extinderea ariei de predicție a legii seriei omologice a variabilității ereditare: cunoscând severitatea factorului de formare a morfologice pentru seria omologică a unei specii, se poate presupune timpul și locația formelor paralele în alte specii înrudite.

In the presented work, using the example of carotenoids and tetrapyrroles, the environmental conditionality of plastid pigment synthesis is substantiated. In the homologous series of the genus Viola, it is shown that the genetically determined synthesis of carotenoids and tetrapyrroles is an adaptation to the circadian rhythms of solar radiation and to variations in its quantitative and qualitative characteristics. An attempt is made to expand the area of prediction of the homological series law in hereditary variability, namely, knowing expression of the morph-forming factor for the homological series of one species, one can assume the time and location of parallel forms in other related species.
Influence of seasonal and latitude changes in solar radiation on the synthesis of plastid pigments
Keywords: carotenoizi; tetrapiroli; radiații; adaptare; radicali; duble legături; spectru; carotenoids; tetrapyrroles; radiation; adaptation; radicals; double bonds; spectrum